Dipole Magnetization Effect to Kerosene Characteristics - Chalid, Mochamad; Saksono, Nelson; Adiwar, Adiwar; Darsono, Nono (Makara Journal of Technology, 2005)
Dipole Magnetization Effect to Kerosene Characteristics. Investigation of kerosene characteristics has been done by ex-situ dipole magnetization. The results show that magnetization technique can be able to influence kerosene characteristics. Polarity and viscosity of the kerosene are observed by measuring refractive index and viscosity. An hour of 4330 Gauss flux magnetic will increase refractive index from 1.447 to 1.449 and decrease the viscosity from 1.278 to 1.256. Those changing support de-clustering occurrence and polarity increment of kerosene molecule. Gas chromatography and infrared result show that those changing do not alter kerosene structure and composition.